Principles of computer security CompTIA security+ and beyond lab manual - Nestler, Vincent J. (New York : McGraw-Hill Osborne Media, 2011)
"Written by leading IT security educators, this fully updated lab ma nual supplements Principles of Computer Security: CompTIA Security+ and Beyond, second edition. Principles of Computer Security Lab Manual, se cond edition, contains more than 30 labs that challenge you to solve re al-world problems with key concepts. Clear, measurable lab objectives m ap to CompTIA Security+ certification exam objectives, ensuring clear c orrespondence to Principles of Computer Security: CompTIA Security+ and Beyond, Second Edition.The Lab Manual also includes materials lists an d lab set-up instructions. Step-by-step, not click-by click, lab scenar ios require you to think critically, and Hint and Warning icons aid you through potentially tricky situations. Post-lab observation questions measure your understanding of lab results and the key term quiz helps t o build vocabulary. Principles of Computer Security Lab Manual, second edition, features: new, more dynamic design and a larger trim size, the real-world, hands-on practice you need to pass the certification exam and succeed on the job Lab solutions on the textbook OLC (Online Learni ng Center). All-inclusive coverage: Introduction and Security Trends; General Security Concepts; Operational/Organizational Security; The Rol e of People in Security; Cryptography; Public Key Infrastructure; Stand ards and Protocols; Physical Security; Network Fundamentals; Infrastruc ture Security; Authentication and Remote Access; Wireless Security; Int rusion Detection Systems and Network Security; Baselines; Types of Atta cks and Malicious Software; E-mail and Instant Messaging; Web Component s; Secure Software Development; Disaster Recovery, Business Continuity, and Organizational Policies; Risk Management; Change Management; Privi lege Management; Computer Forensics; Legal Issues and Ethics; Privacy"- -
Rev. ed. of: Computer security lab manual. c2006.
Catalography
Keywords: Computer security -- Management -- Handbooks, manuals, etc; Data protection -- Handbooks, manuals, etc